Analisis Bibliometrik: Fokus Penelitian Critical Thinking pada Sekolah Menengah (1992-2023) - Siregar, Kartika Dwi Pratiwi; Ramadhaniyati, Resti; Muhammad, Ilham; Triansyah, Fadli Agus (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Critical Thinking is a process that involves mental operations such as deduction, induction, classification, evaluation, and reasoning. This study aims to capture the landscape of Critical Thinking research, especially in secondary schools. The method used is descriptive bibliometric analysis. The source data obtained comes from the Scopus database. The study results show that the most publications related to Critical Thinking are in high schools, namely in 2022, with a total of 18 publications. The publication with the most citations was in 2004, which was cited 133 times. The country that has had the greatest impact on Critical Thinking research in secondary schools in the United States of America. The research focus is divided into sections, namely, 1) development and technology; 2) science and outcomes; 3) curriculum and mathematics, and 4) environment and motivation. The new themes in this field are self-efficacy, STEM education, and innovation. The keywords innovation and Critical Thinking in high school are separate from the other two new theme keywords, self-efficacy and STEM education. The keywords in the first research focus, namely technology and Critical Thinking in high schools, are separate from the keyword reasoning